Identification of separated lenticular planes using optical coherence tomography. Issue 5 (September 2020) - Zheng, Ke; Han, Tian; Zhao, Feng; Han, Yinan; Zhou, Xingtao
Purpose: To discuss how optical coherence tomography can be used to identify separated lenticular planes during small incision lenticule extraction (SMILE). Methods: SMILE procedures were performed on 26 eyes of 13 patients. An anterior segment optical coherence tomography examination was performed after laser scan. Anterior segment optical coherence tomography examinations were conducted again both after separation of the anterior lenticular plane in the right eye and after separation of the posterior lenticular plane in the left eye. Lenticule extraction was then completed, followed by another anterior segment optical coherence tomography examination. Anterior segment optical coherence tomography was also conducted on both eyes on the first day after surgery. Each measurement consisted of four line scans along the 45°, 90°, 135°, and 180° meridians. The brightness scores were compared between the two planes after the separation of one plane. Results: Anterior segment optical coherence tomography showed two bright lines after laser scan. Along with all meridians, the brightness of the anterior plane was less in the right eye, for which only the anterior plane was separated, and the brightness of the posterior plane was less in the left eye, for which only the posterior plane was separated (all P < 0.001). After lenticule extraction in both eyes, anterior segment optical coherence tomography revealed that a smooth hyperreflective line existed between the cap and the residual stromal bed, and this line remained throughout the first day after surgery. Conclusion: The bubbles produced by the creation of the lenticule in SMILE mostly disappear by manual separation, and anterior segment optical coherence tomography can help the surgeon identify the separated lenticular planes.